Implementasi Etika Politik Islam dalam Menghadapi Fenomena Post-Truth dan Disinformasi di Media Sosial: Sebuah Studi Literatur - Arsyan Radifan; Aulia Rahmawati; Farhat Aji Furqon; Muhammad Fauzaan Adji Lesmana; Nurul A'ini; Regina Ramadhania; Edi Suresman (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
The era of digital disruption has given birth to the phenomenon of post-truth and massive disinformation, which triggers sharp political polarization on social media, thereby threatening democratic stability and social integration in Indonesia. This study aims to analyze the effectiveness of implementing Islamic political ethics (Siyasah Syar’iyah) and the transformation of Tabayyun values as instruments for mitigating information disorder in the digital public sphere. The rationale for this research is the urgent need for a robust ethical framework to complement technical-secular digital literacy, which has been deemed insufficient in curbing emotional sentiments and religious hoaxes. The research method employed is qualitative with a library research approach, integrating various contemporary scientific references from the last five years (2020-2025). The research findings indicate that Islamic political ethics offers a holistic solution through the reconstruction of transcendental values in cyberspace activities. The main finding (novelty) of this research is the "Cyber Activism Based on Amar Ma’ruf Nahi Munkar" model, which synergizes the role of Islamic Religious Education (PAI), revelation-based media literacy, and moderate-characterized digital leadership. This model transforms netizens from mere information consumers into agents of "Digital Piety" who actively produce counter-narratives to create a civilized and integrated digital ecosystem.